Invisibilised realities: poverty and impact of the crisis on women a feminist research study in the Barcelona metropolitan area - Sales Gutiérrez, Laura (Cuadernos de Relaciones Laborales, 2013)
This article sets out a critical feminist analysis of poverty and the economic crisis, based a quantitative qualitative research carried out in 2009 with 2,609 women in the Barcelona metropolitan area. it begins with a critical analysis of the concept of poverty, which challenges conventional methods of calculating the poverty rate. it also refers to several aspects of the invisible differential impact of the economic crisis on women, in terms of women’s unemployment and its quality, and a process of recasualization of women's work and increased obligations in care work. These impacts are shown with employment statistics and the conclusion of the research carried out by the surt foundation.
Keywords: feminist analysis; crisis; poverty; women